Unveiling the Biochemical, Enzymatic and Hormonal Stress Biomarkers: Effects of Transportation and Lairage on Sheep Welfare and the Meat Quality - Govindaiah, Prasad M; Maheswarappa, Naveena B; Banerjee, Rituparna; Mishra, Bidyut Prava; Manohar, Balaji B (Journal of Meat Science, 2023)
The objective of this study was to assess the impact of transportation and lairage on biochemical, enzymatic, hormonal changes, and meat quality in Nellore Jodipi sheep. Blood samples were collected from two groups of sheep, L0 (slaughtered immediately after transportation without rest) and L12 (12 h of lairage) during exsanguination to analyze biochemical (blood glucose, creatinine, and total protein), enzymatic (creatine kinase [CK], lactate dehydrogenase [LDH], aspartate transaminase [AST], and alanine aminotransferase [ALT]), and hormonal (cortisol, triiodothyronine [T3], and thyroxine [T4]) parameters. Meat samples from the longissimus dorsi muscle were examined for pH, r value, instrumental color, water holding capacity (WHC), shear force, drip loss, cooking loss, and thiobarbituric acid reactive substances (TBARS). Lower (P
Keywords: Welfare; Stress Biomarkers; Transportation; Lairage; Sheep